Inadequate birth spacing is perceived as riskier than all family planning methods, except sterilization and abortion, in a qualitative study among urban Nigerians - Hilary M. Schwandt; Joanna Skinner; Luciana Estelle Hebert; Lisa Cobb; Abdulmumin Saad; Mojisola Odeku (BMC, 2017)
Abstract Background Fertility is high in Nigeria and contraceptive use is low. Little is known about how urban Nigerians perceive the risk of contraceptive use in relation to pregnancy and birth. This study examines and compares the risk perception of family planning methods and pregnancy related scenarios among urban Nigerians. Methods A total of 26 focus group discussions with 243 participants were conducted in September and October 2010 in Ibadan and Kaduna. The groups were stratified by sex, age, family planning use, and city. Study participants were asked to identify the risk associated with six different family planning methods and four pregnancy related risks. The data were coded in ATLAS.ti 6 and analyzed using the thematic content analysis approach. Results The ten family planning and pregnancy related items ranked as follows from most to least risky: sterilization, abortion, getting pregnant soon after having a baby (no birth spacing), pill, IUD, injectable, having a birth under 18 years of age (teenage motherhood), condom use, having six children, and fertility awareness methods. Risk of family planning methods was often categorized in terms of side effects and complications. Positive perceptions of teenage motherhood and having many children influenced the low ranking of these items. Conclusion Inadequate birth spacing was rated as more risky than all contraceptive methods and pregnancy related events except for sterilization and abortion. Some of the participants' risk perceptions of contraceptives and pregnancy related scenarios does not correspond to actual risk of methods and practices. Instead, the items' perceived riskiness largely correspond with prevailing social norms. However, there was a high level of understanding of the risks of inadequate birth spacing. Trial registration Number: This study is not a randomized control trial so the study has not been registered as such.